Self-Enforcing Climate Coalitions for Farsighted Countries: Integrated Analysis of Heterogeneous Countries - Sareh Vosooghi; Maria Arvaniti; Rick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the formation of international climate coalitions by heterogeneous countries. Countries rationally predict the consequences of their membership decisions in climate negotiations. We offer an approach to characterise the equilibrium number of coalitions and their number of signatories independent of their heterogeneity, and we suggest a tractable algorithm to fully characterise the equilibrium. In a dynamic game analysis of a general equilibrium model of the economy integrated with climate dynamics, a grand climate coalition or multiple climate coalitions may form in equilibrium, but if the policymakers are patient, the number of signatories in all climate treaties is a Tribonacci number. Our results are robust to the possibility of renegotiation and investment in green technologies besides fossil fuels.
Keywords: Q54; D70; D50; 330; climate economics; international environmental agreements; coalition formation; heterogeneous countries; integrated assessment models